(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2025)
The article analyzes the sociocultural and psychological determinants of vaccine resistance in adults aged 19 to 64 years, through a literature review, with a qualitative-descriptive approach. Important aspects that influence reluctance to immunization in adults of this age range were identified. Among the sociocultural determinants, religion, education, beliefs and cultural traditions were noted; on the other hand, among the psychological factors, fear, misinformation and the perception of the risk of the side effects of vaccines were identified with great predominance. The findings showed that, despite the scientific information supporting the effectiveness and safety of vaccines provided by governments, agencies and health institutions , there are barriers to acceptance, motivated by lack of confidence in the safety of vaccines and fear, especially among young adults, of side effects, who even underestimate the risks of diseases. The review also showed that the influence of family, social groups and friends has a high impact on the decision of adults towards immunization. The literature analysis and interpretation highlighted the importance of addressing and understanding the sociocultural and psychological determinants of the adult population aged 19 to 64 years and understanding that the acceptance of immunization varies according to the age range, where adults older than 40 years showed greater awareness; and those younger than this age present greater doubts and fears.